2020
DOI: 10.1108/oir-03-2020-0116
|View full text |Cite
|
Sign up to set email alerts
|

User motivation in fake news sharing during the COVID-19 pandemic: an application of the uses and gratification theory

Abstract: PurposeThis study developed a predictive model that established the user motivational factors that predict COVID-19 fake news sharing on social media.Design/methodology/approachThe partial least squares structural equation modelling (PLS-SEM) was used for the analysis. Data were drawn from 152 Facebook and WhatsApp users in Nigeria to examine the research model formulated using the uses and gratification theory (UGT).FindingsWe found that altruism, instant news sharing, socialisation and self-promotion predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 62 publications
6
95
2
1
Order By: Relevance
“…For example, Islam et al found that entertainment and self-promotion could promote the sharing of misinformation about COVID-19 [18]. Apuke and Omar found that altruism, instant news sharing, socialisation predicted fake news sharing related to the COVID-19 pandemic among social media users in Nigeria [19]. Laato et al suggested that a person's trust in online information and perceived information overload were strong predictors of unverified information sharing [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Islam et al found that entertainment and self-promotion could promote the sharing of misinformation about COVID-19 [18]. Apuke and Omar found that altruism, instant news sharing, socialisation predicted fake news sharing related to the COVID-19 pandemic among social media users in Nigeria [19]. Laato et al suggested that a person's trust in online information and perceived information overload were strong predictors of unverified information sharing [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The level of scientific knowledge of users during public health emergencies refers to the basic literacy of individuals on health information and their ability to generate health information spreading behaviors in health crisis situations ( Fu et al., 2017 ; Nutbeam, 2000 ; Wood, 2018 ). Various models have considered the role of users' level of scientific knowledge on their willingness and ability to share online rumors ( Apuke & Omar, 2020 ; Suri et al., 2016 ); some scientists believe that a lack of scientific knowledge is one of the internal driving factors for the spread of rumors online ( Huo & Chen, 2020 ). In general, the level of scientific knowledge will affect the user's perceived risk efficiency and thus affect the user's behavioral decisions regarding the spread of online rumors and rumor-refuting information.…”
Section: Discussionmentioning
confidence: 99%
“…Due to different goals, individuals have different needs when obtaining information, so they selectively adopt the information they perceive to be useful [ 46 ]. The perceived usefulness of COVID-19 videos with different content is different, which is reflected in the difference in their popularity [ 27 ]. Therefore, the content type of the video is related to the perceived usefulness of the information.…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…Popularity level can be used to express the results of information adoption. In the study of YouTube, popularity level was measured by views and the level of positive feedback (e.g., liking rate(likes/(likes + dislikes) × 100)) [ 25 , 27 , 63 ]. The measurement index of audience feedback is determined according to the ways that audiences can socialize on the platform.…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation